The political economy of the media in the Somali conflict. Issue 147 (2nd January 2016) - Stremlau, Nicole; Fantini, Emanuele; Osman, Ridwan M.
Abstract : This article explores the political economy of the media in the context of weak formal state institutions in Somalia. Drawing on literature examining the political economy of war, the authors argue that, rather than being either a system of anarchy or a system in which journalists strive to serve normative functions of a fourth estate, the media in Somalia have their own internal logic that operates according to local norms and rules. This accounts for the media's ability to continue to grow despite the serious security concerns and the absence of strong state institutions and regulations, as well as predictable and regular revenue.